PENERAPAN PERSAMAAN SIMULTAN PADA ANALISIS HUBUNGAN PRODUKSI PADI DAN KONSUMSI BERAS UNTUK MELIHAT KONDISI KETAHANAN PANGAN STUDI KASUS INDONESIA TAHUN 2024 - Rahmad Fradani, Faisal Agymnastiar; Nafisah Zahra; Tenry Kusuma Astuti; Aulia Rahmi Al Muqorobbun; Nindya Faristanti; Laksmi Yustika Devi (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to analyse the simultaneous relationship between rice production and rice consumption in order to review Indonesia's food security conditions in 2024. The method used is Two Stage Least Squares (2SLS) in a simultaneous equation model, with secondary data from 34 provinces. The estimation results indicate that there is a simultaneous relationship between rice consumption and rice production. However, only rice consumption has been proven to have a significant effect on rice production. This means that an increase in rice consumption by the public drives an increase in rice production, while an increase in rice production does not directly affect the level of rice consumption by the public. Every 1% increase in consumption will drive rice production up by 0.114765%. Harvest area also has a significant effect, with a 1% increase in harvest area resulting in a 1.078499% increase in production. On the consumption side, only population density has a significant impact, increasing rice consumption by 0.441294%. The model has met the classical assumption tests and model validity, so the results can be trusted. These findings highlight the importance of maintaining a balance between consumption and production to support sustainable national food security.